Assessment of digital therapeutics in decentralized clinical trials: A scoping review. - Cinja Koller; Marc Blanchard; Thomas Hügle (PLOS Digital Health, 2025)
This scoping review aims to identify the necessary and practical considerations for the design, conduct and safety of decentralized clinical trials (DCTs) that test digital therapeutics (DTx) or software as a medical device (SaMD). The review follows the framework of Arksey & O'Malley. A search strategy with the keywords "Digital therapeutics" or "Software as Medical Device" AND "decentralized clinical trial" or synonyms was applied to Cochrane CENTRAL, EMBASE, MEDLINE and Web of Science databases with the latest search on the 25th of April 2025. We selected peer-reviewed articles reporting about fully or partly DCTs using apps or devices that were classified as DTx or SaMD. Studies using general health software or not focusing on the design or experiences of the DCT were excluded. Main study characteristics were extracted and the articles thematically coded with the qualitative software Atlas.ti. 335 results were assessed for title and abstract screening and 113 articles were identified for full-text screening, of those 41 fulfilled inclusion criteria. DTx used in the trials were mainly targeting depression. The clinical trial design differed significantly in the number of study arms (1-16), participants (11─5602) and blinding. E-recruitment (78%), e-eligibility screening (73%), e-informed consent (68%), inclusion of electronic-patient reported outcomes (e-PROs) (88%), passive data collection (59%) and use of reminders (59%) were key reoccurring features of the studies. Effective access and inclusion of participants, but low adherence and engagement is highlighted in most studies. In some cases, only 40% of participants installed the app and significant drop-out rates of about 50% are reported. A framework for DCTs evaluating DTx is provided. In summary, DCTs for DTx are unstandardized, heterogenous and characterized by low adherence. Further research on how to tackle the engagement problem, along with clearer guidance and regulatory frameworks, is required to standardize this trial type in the future.